Entrevista com Alexandre Barbosa de Souza - Costa, Patrícia Rodrigues (2021)
Alexandre Barbosa de Souza is a writer, poet, editor and translator. He was editor at Editora 34, Cosac Naify, and Biblioteca Azul. He is the author of Azul Escuro (Hedra, 2003), Autobiografia de um super-herói (Hedra, 2003), and Livro geral (Companhia das Letras, 2013). Also, he translates from English, French and Spanish. Among his translations we can cite: Moby Dick (Cosac Naify, 2008), by Herman Melville; A crônica dos Wapshot (Companhia das Letras, 2011), by John Cheever; Orgulho e Preconceito (Companhia das Letras, 2011) and Razão e Sensibilidade (Companhia das Letras, 2012), by Jane Austen; Alice através do espelho (SESI-SP, 2018); Só garotos (Companhia das Letras, 2018), by Patti Smith; Anne de Green Gables (Editora Nova Fronteira, 2019), by L. M. Montegomery.